(untitled) (Veterinária Notícias, 2020)
This study aimed to assess the corn silage used in 31 dairy farms in the municipality of Patos de Minas, State of Minas Gerais, Brazil. A questionnaire was applied with questions related to the property, the silage process, and the use of roughage. A cluster analysis was then performed to group the properties using the centroid method. Data were submitted to analysis of variance in a completely randomized design. The continuous variables and the discrete variables had their means compared using the Tukey test and the chi-square test, respectively, with 5% probability of type I error. Properties with low milk production were those with no technical assistance; they tended to have nonuniform silo faces and manual removal of silage, resulting in higher silage loss.